Michael Sadler and comparative education - Phillips, D (2006)
This paper examines the work in education of Michael Sadler (1861-1943). It covers his early years in Oxford, his time as director of the Department of Special Inquiries and Reports, his periods as professor of education in Manchester and as vice-chancellor in Leeds, and his return to Oxford as Master of University College, and it assesses the significance of his contribution to the early development of comparative studies in education and its continuing relevance.